Acceptance and Commitment Therapy in a Low-Income Country in Sub-Saharan Africa: A Call for Further Research - Geda, Yonas E.; Krell-Roesch, Janina; Fisseha, Yaphet; Tefera, Aida; Beyero, Teferra; Rosenbaum, Deborah; Szabo, Thomas G.; Araya, Mesfin; Hayes, Steven C. (Frontiers in Public Health, 2021)
A worsening trend of critical shortages in senior health care workers across low- and middle-income countries (LMICs) in sub-Saharan Africa has been documented for decades. This is especially the case in Ethiopia that has severe shortage of mental health professionals. Consistent with the WHO recommended approach of task sharing for mental health care in LMICs, Acceptance and Commitment Therapy (ACT), which is an empirically validated psychological intervention aimed at increasing psychological flexibility, may be delivered by trained laypersons who have a grassroots presence. In this paper, we discuss the need for and potential role of ACT to be delivered by health extension workers (HEWs) to address mental health care needs across Ethiopia. To this end, we also reviewed previous studies that have examined the effectiveness of ACT-based interventions in African countries including in Nigeria, Sierra Leone, Uganda, and South Africa. All studies revealed significant improvements of various mental health-related outcome measures such as decreased psychological distress and depressive symptoms, or increased subjective wellbeing and life satisfaction in the groups that received an ACT-based intervention. However, to date, there is no study that applied ACT in Ethiopia. Thus, more research is warranted to examine the effectiveness and, if proven successful, to scale up a task sharing approach of an ACT-based intervention being delivered by trained HEWs at a grassroots level, possibly paving the way for an innovative, sustainable mental health service in Ethiopia as well as other African LMICs.